1925 Ind. Acts 497 § 9 - (:unkn) unknown (General Publisher, 1925)
Prohiited the sale, delivery, or otherwise transfer of a pistol or revolver to a person who he or she has reasonable cause believe is either not a citizen or is a felon. Violatos fined not less than one hundred dollars, or imprisoned not more than one year, or both.
--
Keywords: TRANSFER - DANGEROUS PERSONS